Health literacy and its role in the care for health of the Roma and of persons living poverty line - Maňhalová, Jana; null, null; Kajanová, Alena (STEF92 Technology Ltd., 2018)
Background: Health literacy, which is a part of the fundamental equipment for life and the path to the health of the individual and of the society, has been coming to the foreground of many scientific disciplines in recent years. The crucial issue of the presented area consists in the fact that low health literacy is a serious risk factor for health, which deepens undesirable health inequalities and results in high costs for health care. The goal of this article consists in presenting partial results of a study mapping the health literacy of selected groups of population of South Bohemian Region and in showing health literacy and its role in the care for health among the Roma and persons below poverty line living in South Bohemian Region, Czech Republic. Methods: The submitted article presents partial results of the RVO ZSF JU project called Health literacy of selected groups of population of South Bohemian Region (SDZ2016), implemented in 2016-2019. The study was implemented through quantitative research, preceded by qualitative scientific approach implemented with the help of semi-structured interview. The quantitative research was implemented with the help of the short form of the standardized 16-item HLS-EU questionnaire intended for identification of health literacy of the population. The data collection was implemented in two target groups, specifically among persons who identify themselves as Roma and among persons below poverty line living in the South Bohemian Region. The respondents were selected with the help of snowball sampling method. Results: The results of the descriptive analysis revealed an average point score of 10,22 among the Roma and 10,16 among persons living below poverty line; so it can be placed at the upper limit of problematic health literacy, which ranges from 9 to 12 points. Based on the calculation of health literacy index, calculated only from complete answers of the respondents (Roma - n = 135, persons below poverty line – n = 204), it can be stated that inadequate (insufficient) health literacy was found in 31.1% of the Roma and in 31.9% of persons living below poverty line; problematic health literacy was found in 31.1% of the Roma and in 34.3% of persons living below poverty line; and sufficient health literacy was found in 37.8% of the Roma and in 33.8% of persons living below poverty line. Conclusion: Our qualitative research shows a trend revealing the weaknesses of this issue in connection with both target groups. The key barriers affecting the health literacy of the Roma and of persons living below poverty line include insufficient information on health, health situation and health system, insufficient motivation and activities aimed at searching information on health and insufficient cognitive and affective abilities to find and understand information on health condition. The results of the quantitative research bring the calculation of the health literacy index, dividing it into inadequate, problematic and sufficient; inadequate health literacy found in both target groups exceeded 30.0%.
Keywords: health literacy; health; Roma; persons living below poverty line